Zebrafish Models for Development and Disease 2.0 - Marrs, James A.; Sarmah, Swapnalee (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The special issue (Zebrafish Models for Development and Disease 2.0) is a collection of articles highlighting research using the zebrafish (Danio rerio) experimental organism. Research described in this special issue addresses various developmental biology, genetic, biomedical and neuroscience topics that should be of general interest to the biomedical research community.